Defensio verae translationis corporis Catechismi in linguam Polonicam, adversus calumnias Joannis Secluciani Jana Maleckiego – przekład wraz z komentarzem - Lenartowicz-Zagrodna, Anna (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The response written by Jan Sandecki-Malecki provides extremely important information on the sixteenth century Polish language as it is the only meta-linguistic statement from the period available in full that has been preserved until our times. The text originated as the response that took the form of a manuscript work "A Defense,against the calumnies of jan Seklucjan, of the true translation of the Body of the Catechism into the Polish language" in which Malecki answered Seklucjan’s criticism in a debate centered on the proper translation of a number of passages from Scripture and contributed to the controversy between Jan Seklucjan (Seclucianus) and Malecki over the proper translation of Holy Scripture in Polish; it constitutes a polemic against the critical remarks on the Polish translation of the catechism. Being a voice and opinion on the issues related to the contemporary state and needs of the Polish language of the time, given by a member of the then intellectual elite, "Defensio…" illustrates well the sixteenth century linguistic competence. On the basis of the latter it is possible to reconstruct the Renaissance shape of literary Polish and evaluate its stylistic value.
Jan Malecki’s The Defensio verae translationis corporis Catechismi in linguam Polonicam, adversus calumnias Joannis Secluciani – annotated translation
Keywords: polszczyzna XVI wieku; Jan Sandecki-Malecki; Katechizm polski